Cleaner production implementation in the textile sector: The case of a medium-sized industry in Minas Gerais - Costa, Nelma Penha da; Prado Filho, José Francisco; Fonseca, Alberto (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
Textile industries have been increasingly adopting cleaner production strategies, particularly in developed countries. In Brazil and globally, there are arguably few publications addressing this phenomenon. This study aimed at understanding the extent to which industries from textile sector implement cleaner production strategies, based on the empirical analysis of a particular medium-sized industry in the state of Minas Gerais, Brazil. A checklist of cleaner production opportunities, drawn from the literature, was analyzed in the context of the selected industry. Data were collected through interviews and field surveys. This study identified cleaner production opportunities for textiles industries and pointed out a number most viable actions. The study also identified that cleaner production can work as an effective environmental management framework for medium-sized industries. However, depending on the particular aspects of each industry, cleaner production actions may be perceived as technically and economically unviable. In the particular case study, the most implemented actions were those that required lower investments and that were not technically demanding. Results suggest that cleaner production can drive proactive environmental efforts, resulting in technological and economic benefits. However, results also suggest that such benefits may not be easily obtained, particularly in the context of industries with out-of-date technological processes.